ナンキョク コショウ ツウネン カンソクヨウ ビデオカメラシステム ノ カイハツ ト セッチ - 工藤, 栄; クドウ, サカエ; 田邊, 優貴子; タナベ, ユキコ; 内田, 雅己; ウチダ, マサキ; 掘, 克博; ホリ, カツヒロ; Kudoh, Sakae; Tanabe, Yukiko; Uchida, Masaki; Hori, Katsuhiro (2010)
P(論文) 南極湖沼中に設置し,湖底の植物群落の1年にわたる映像記録を捉える目的で水中ビデオシステムの開発を行った. システムはビデオカメラ,制御部,レンズ汚濁防止ワイパー(水中モーター),照明用LEDとリチウム電池から構成されたものである. 市販のハイビジョン方式のビデオを採用し,レンズ汚濁防止ワイパーの動作を簡潔化して,以前試作したビデオシステムよりも消費電力を増やすことなく記録感度を向上させることができた. この機材を第51次日本南極地域観測隊夏行動期間中に,宗谷海岸のスカルブスネス「長池(仮称)」湖底に潜水作業により設置し,一年間の湖底のインターバル撮影を開始した. A submersible video camera system, which aimed to record the growth image of aquatic vegetation in Antarctic lakes for one year, was manufactured. The system consisted of a video camera, a programmable controller unit, a lens-cleaning wiper with a submersible motor, LED lights, and a lithium ion battery unit. Changes of video camera (High Vision System) and modification of the lens-cleaning wiper allowed higher sensitivity and clearer recording images compared to the previous submersible video without increasing the power consumption. This system was set on the lake floor in Lake Naga Ike (a tentative name) in Skarvsnes in Soya Coast, during the summer activity of the 51th Japanese Antarctic Research Expedition. Interval record of underwater visual image for one year have been started by our diving operation. departmental bulletin paper